The Relationship between the Verbal Composition of a Language and the Mental Image of the Speaker or Writer - Althory, Abdallah Ali (Arab Journal for Sciences and Research Publishing, 2021)
The study aimed to identify the relationship between the verbal composition and the mental image of a speaker or a writer since the speech varies or differentiates in composition and connotation according to the harmony between verbal embodiment and the intended meanings. The study also attempts to explore the nature of the choice of words, structures and methods that are the pictorial tools for the hidden meaning of the speaker or writer of the language or the hidden meaning of whoever speaks in his name or expresses his condition, as well as examine the formation of those words, structures and methods in a way that fulfills the ultimate goal of embodying the meaning. In addition to the basic stage in the formation of the linguistic structure system, which is formation of the psychological image that the speaker wants to embody through verbal composition and how to arrange it. In order to achieve the study objectives, the inductive descriptive method was used which is fit the nature of the study and its procedures with special emphasis on the references. The study revealed that the differentiation in meaning between the compositions and words is based on the accuracy of the psychological and mental image existing in the mind of the speaker, and on the good verbal use that is commensurate with that image when expressing it. In light of the findings, the conducting study recommended to conduct further linguistic studies that clarify the foundations of linguistic proportionality between the psychological and mental image, and its verbal representation at the morphological, structural and semantic level.